2022
DOI: 10.3389/fpubh.2022.923324
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on birth outcomes: A retrospective cohort study in Nanjing, China

Abstract: IntroductionThe coronavirus disease 2019 (COVID-19) pandemic have significantly affected health care systems and daily wellbeing. However, the indirect impacts of the pandemic on birth outcomes are not fully understood. We aimed to examine whether the pandemic altered risk of adverse birth outcomes.MethodsThis retrospective cohort study included all singleton births during 2016–2020 identified in Women's Hospital of Nanjing Medical University. We compared birth outcomes during COVID-19 pandemic (January–Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…COVID-19 infection during pregnancy is associated with an increased risk of premature birth by 3.34 times and caesarean section by 3.63 times. However, the infant in this report was confirmed to be negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and have no abnormal computed tomography (CT) results (Wen, 2022). The majority of premature births are attributed to iatrogenic causes and are not associated with preterm premature rupture of membranes (PPROM), which occurs four times more frequently in pregnant women who tested positive for SARS-CoV-2…”
Section: Discussionmentioning
confidence: 80%
“…COVID-19 infection during pregnancy is associated with an increased risk of premature birth by 3.34 times and caesarean section by 3.63 times. However, the infant in this report was confirmed to be negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and have no abnormal computed tomography (CT) results (Wen, 2022). The majority of premature births are attributed to iatrogenic causes and are not associated with preterm premature rupture of membranes (PPROM), which occurs four times more frequently in pregnant women who tested positive for SARS-CoV-2…”
Section: Discussionmentioning
confidence: 80%
“…Also, Smith et al [15] noticed that 63.8%, 42.8% of cases had preterm births, low birth weight, respectively. Wen [25] reported that low birth weight was 1.13 folds higher among cases. PROM and preterm labor might be spontaneous; could be justified by activation of biochemical pathways and inflammatory mediators (play an important role in PROM and preterm labor), which is associated with SARS-CoV-2 infection, among these cytokines, circulating IL-6 that is closely linked to SARS-CoV-2 infection severity [26,27] , or iatrogenic; with the goal of enhancing maternal oxygenation with delivery [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding PROM, preterm labor and low birth weight, various studies focused on increased risk of them [14, 19,20,25] . PROM was 1.7 times higher among cases [21] .…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the study, it was shown that COVID-19 led to increases in adverse pregnancy outcomes, such as preterm birth and cesarean delivery, but insufficient evidence regarding placental transmission of SARS-COV-2 is available [9]. In a study conducted in Nanjing, China, it was observed that no change in preterm birth during the pandemic occurred, but a decrease in birth weight in term babies had occurred, and it was thought that anxiety and stress caused by the pandemic may also contribute to this lower weight [10]. A systematic meta-analysis review study found that low birth weight rates in neonates are more common in pregnancy with severe COVID-19 [11].…”
Section: Discussionmentioning
confidence: 99%